Shaping the future of urban mobility - potentiating car alternatives, increasing environmental and socioeconomic welfare given car usage and the rise of electric vehicles - Campos, Nuno Rafael Rego (2020)
Mass transport and sof tmodesplay a critical role in solving the major it yofurb an mobility problems that emerged in the last decades. Despite the benefits of the se transportation types, their usage in Portugal is still below its European peer san dfurther below the desired levels. The car usagere duction, particularly in city centers, should be amain concern of decision-makersasitinterferesinsocialwelfare.Havingtodealwiththecar,alternatively-poweredvehiclesappearasasolutiontofacetheenvironmentalproblemsraisedbytheexcessiveGHGemissionstotheatmosphere.